Evaluating Security Standards and Frameworks for IoT-Enabled Smart Environments - Lungu, Matthew; Mbale, Jameson (Proceedings of International Conference for ICT (ICICT) - Zambia, 2025)
The rapid expansion of IoT-enabled smart environments, such as smart homes and cities, brings notable benefits in efficiency, convenience, and sustainability. However, these advancements also introduce significant security risks as the growing interconnectivity of IoT devices increases their vulnerability to threats like data breaches, device hijacking, and DDoS attacks. Ensuring the security of these environments is crucial to mitigate risks and implement effective controls. Despite the urgent need for comprehensive security frameworks, a significant gap remains in identifying standards and methodologies that address the unique and evolving security challenges of IoT-based systems. This paper aims to address this gap by conducting an extensive review of existing security standards and assessment frameworks, with a particular focus on NIST’s (National Institute of Standards and Technology) special publications on security techniques, including those still under development. By analysing their strengths, weaknesses, and areas of focus, the study identifies which frameworks are most suited for IoT-based smart environments. Additionally, it evaluates the practical application of these frameworks in real-world scenarios, examining their ability to uncover vulnerabilities, assess security postures, and guide the implementation of effective countermeasures. The findings highlight that while traditional security frameworks may not fully address the unique challenges of IoT environments, they can be adapted to meet these needs. This paper provides insights for researchers, industry practitioners, and policymakers and paves the way for future research to develop tailored security standards and frameworks. It also discusses the key challenges facing IoT security and offers a roadmap for advancing the safe, secure, and sustainable deployment of IoT technologies.